2020
DOI: 10.1158/1535-7163.mct-19-0505
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Mechanism ERK1/2 Inhibitors Exploit a Distinct Binding Mode to Block Phosphorylation and Nuclear Accumulation of ERK1/2

Abstract: The RAS-regulated RAF-MEK1/2-ERK1/2 signaling pathway is frequently deregulated in cancer due to activating mutations of growth factor receptors, RAS or BRAF. Both RAF and MEK1/2 inhibitors are clinically approved and various ERK1/2 inhibitors (ERKi) are currently undergoing clinical trials. To date, ERKi display two distinct mechanisms of action (MoA): catalytic ERKi solely inhibit ERK1/2 catalytic activity, whereas dual mechanism ERKi additionally prevents the activating phosphorylation of ERK1/2 at its T-E-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 48 publications
(85 reference statements)
1
29
0
Order By: Relevance
“…Thus, ERK T188 -phosphorylation and subsequent nuclear ERK localization/accumulation are key determinants of gene expression and ERK-mediated pathological cardiomyocyte hypertrophy. Selective interference with ERK T188 -phosphorylation or ERK dimerization, in contrast to global ERK1/2 kinase inhibition and presumably also ERK kinase inhibitors 51 , offers the possibility to preserve beneficial cytosolic, and to specifically interfere with maladaptive nuclear ERK1/2 signaling in cardiomyocytes. The strong effect of EDI on gene regulation and thus cardiac remodeling as well as cancer cell proliferation may be due to direct or indirect activation of nuclear transcription factors by ERK1/2, but also kinase-independent ERK1/2 effects such as a direct binding of ERK to oligonucleotides, as shown for ERK2, activated ERK2, and ERK2 T188D (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ERK T188 -phosphorylation and subsequent nuclear ERK localization/accumulation are key determinants of gene expression and ERK-mediated pathological cardiomyocyte hypertrophy. Selective interference with ERK T188 -phosphorylation or ERK dimerization, in contrast to global ERK1/2 kinase inhibition and presumably also ERK kinase inhibitors 51 , offers the possibility to preserve beneficial cytosolic, and to specifically interfere with maladaptive nuclear ERK1/2 signaling in cardiomyocytes. The strong effect of EDI on gene regulation and thus cardiac remodeling as well as cancer cell proliferation may be due to direct or indirect activation of nuclear transcription factors by ERK1/2, but also kinase-independent ERK1/2 effects such as a direct binding of ERK to oligonucleotides, as shown for ERK2, activated ERK2, and ERK2 T188D (ref.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have suggested that the differing abilities of ERK inhibitors to prevent the phosphorylation of ERK is related to their binding modes (28,30). The mechanism by which this distinctive ERK-binding mode leads to a decrease in the phosphorylation of ERK has not previously been defined.…”
Section: Discussionmentioning
confidence: 97%
“…Mol Cancer Ther; 20 (10) October 2021 that GDC-0994, an ERK inhibitor that binds within the ERK active site, but does not extend into the secondary pocket (21,28), did not robustly prevent the phosphorylation of ERK by MEK. As expected, the MEK inhibitor, trametinib, bound directly to MEK while inhibiting the phosphorylation of ERK.…”
Section: Aacrjournalsorgmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed ERKi (SCH772984 and Ulixertinib) achieved synergistic efficacy with sorafenib in RPL22L1-overexpressed cells. The two ERKi display distinct mechanism of action, with Ulixertinib (Catalytic ERKi) solely preventing ERK1/2 catalytic activity while SCH772984 (Dual mechanism ERKi) extra blocking p-ERK1/2 at T-E-Y motif by MEK1/2 [ 34 ]. This probably explained the discrepancy in p-ERK level between the two ERKi.…”
Section: Discussionmentioning
confidence: 99%